Empty hours [videorecording (DVD)] - Fernández, Aarón (Fernández Lesur); Ferrer, Kristyan; Paz, Adriana; Lara Martínez, Eliseo (Strand Releasing Home Video, 2014)
"On the desolated coast of Veracruz, seventeen-year-old Sebastián takes over running his uncle's small and cozy rent-by-the hour motel. There he meets Miranda, a regular customer who comes to the motel to meet a lover who always keeps her waiting. As Sebastián and Miranda get to know each other, an ambiguous game of seduction begins between them"--Container.